2018
DOI: 10.1016/j.catena.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of quarry exploitation and disuse on pedogenesis

Abstract: Quarrying represents one of the oldest and most important human activities; the impacts of which have largely influenced vegetation and landscape. Despite its character as a vital and non-renewable resource, the soil has been poorly studied with regard to either the impact resulting from the exploitation of quarries or its restoration after exploitation. In the plain of La Crau (south-eastern France), numerous dry alluvial quarries were exploited in the 1970s. Their exploitation lasted about ten years and they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
0
14
0
4
Order By: Relevance
“…Although there may be a wide range of soil rehabilitation recommendations, it is essential to conduct a complete ecosystem analysis before site rehabilitation. The analysis must integrate the description of the developed soils and the slow pedogenic processes [16]. Thus, the soils' study under páramo is indispensable to understand the páramo ecosystem's functioning and optimize its ecological rehabilitation efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there may be a wide range of soil rehabilitation recommendations, it is essential to conduct a complete ecosystem analysis before site rehabilitation. The analysis must integrate the description of the developed soils and the slow pedogenic processes [16]. Thus, the soils' study under páramo is indispensable to understand the páramo ecosystem's functioning and optimize its ecological rehabilitation efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the exploitation has been so intensive that only bare soil remains. In this condition, the ecosystem demands an active restoration with direct intervention on the degraded páramo ecosystem's structure and characteristics to overcome stressors that prevent regeneration and ensure recovery [2,7,16,18,32,34]. However, few know how to or even if it is possible to regenerate the NHP, the resilience of NHP, and the resilience of andosols to continue supporting the NHP ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the large number of studies on properties and regimes of waterlogged soils of natural landscapes [19][20][21][22]30], the appearance of soil hydromorphism on the primary soil-forming stage has not been studied enough. Literature analysis has shown that studies on the formation of soil and plant cover in disturbed areas are mainly devoted to the investigation of this process in automorphic conditions [1,7,18,31].…”
Section: Introductionmentioning
confidence: 99%
“…These findings can be extrapolated to other limestone quarries. Restoring a quarry is a complex process -the starting site is generally bare and consists of a low-fertility substrate (Chenot et al 2018). Therefore, in planning a successful succession process, it is important to identify the best restoration approaches.…”
Section: Introductionmentioning
confidence: 99%